Diet and mobility of fauna from Late Neolithic-Chalcolithic site of Perdigões, Portugal - Zalaite, I. (2018)
Perdigões is located in the Alentejo region of south-eastern Portugal, with occupational phases dating from the Late Middle Neolithic to Late Chalcolithic/Early Bronze Age (middle 4th and 3rd millennium BCE) periods. It is a complex site that can be considered as a centre of social aggregation and a part of a larger settlement network. In this study, the nature of animal subsistence patterns as well as husbandry management practices and mobility are examined using stable carbon and nitrogen isotopic values from bone collagen of 35 archaeological faunal samples (Canis familiaris, Bos taurus, Bos primigenius, Sus sp., Ovis/Capra, Cervus elaphus, O. cuniculus, Equus sp.) and strontium isotope (87Sr/86Sr) analysis of 23 enamel samples. To provide necessary biological 87Sr/86Sr baseline data, the strontium isotopic composition of 14 modern plant samples were measured. The stable carbon and nitrogen isotope data shows that animals subsisted on a selection of C3 terrestrial resources, with subtle differences in animal husbandry practices in domesticated animals, while strontium isotope analysis shows that <5% of analysed fauna is consistent with the local bioavailable strontium isotopic range. Other animals can be divided into two clusters – those having strontium isotope values either lower or higher than the bioavailable range, showing that most of the fauna browsed and grazed within 10 km of the site's surrounding landscape, which is not such an unusual practice during prehistoric times.